Prediction of Pavement Performance Using Various Deterioration Models for Patiala Urban Road Network - Kamotra, Sahil (My University, 2017)
The study carried out for the urban road network of Patiala city which are Rajendra Hospital Chowk to YPS Chowk (PR-01), Dhukniwaran Sahib to Thapar University (PR-02) and Tripuri to Kohli Sweets (PR-03) to forecast remaining service life of road with the use of HDM-4 software. Prioritizations of the three sections are done on the basis of the Urban Road Maintenance Priority Index (URMPI) which prioritizes the road section which is in the urgent need of maintenance works. The analysis of cost and maintenance planning is done for the network name Dukhniwaran Sahib Gurudawara to Nabha (NUR-01) road as it is one of the Major District Road of State Punjab. The cost of various maintenance works for different intervention levels is done out of which cost of level 3 of serviceability comes out to be economical. Comparative Study of Scheduled and Condition Responsive type Maintenance & Rehabilitation Strategy is also conducted with the help of HDM-4 model to recognize the most effective intervention. The Scheduled maintenance is not able to limit roughness value and leads to low ride quality of the road network whereas responsive alternatives are maintaining road quality to the accepted level of serviceability. The data have been collected for five sections for cracking, roughness, ravelling, deflection which is used for regression analysis. The Indian pavement deterioration model developed by CRRI was validated by comparing the predicted and observed values for the selected pavement sections. The R2 values obtained for cracking progression (0.7549), ravelling area progression (0.8381) and roughness progression (0.7484) models show good adequacy between observed and predicted values. These pavement deterioration models can be used for prediction of distresses and for development of maintenance management strategies for the selected urban road network.
Master of Engineering -Civil Infrastructures
Keywords: PMMS; priortization; HDM 4; maintenance